Power and Possibility Adult Education in a Diverse and Complex World - Finnegan, Fergal; Grummell, Bernie (Research on the Education and Learning of Adults, 2019)
Power and Possibility: Adult Education in a Diverse and Complex World explores the topic of power and possibility theoretically, historically and practically through a range of perspectives and in relation to varied areas of interest within contemporary adult education. Readership: Adult education researchers and academics, adult education practitioners and policy-makers, postgraduate students and researchers in adult education, education, social movements studies, sociology and politics, organisational studies.